Eldearly Preparedness In Faces Of Tornado Disaster In The District Sitinjo - Risdiana Melinda Naibaho (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
A Tornado is a strong wind or it can also be called a big, very strong storm with a whirlwind at a certain speed. Disasters cannot be predicted at any time and can occur. The need for disaster preparedness to prevent the risk of human casualties, material losses, environmental damage and psychological impacts that threaten and disrupt people's lives and livelihoods. Elderly is a group that is very at risk before, during and after a disaster occurs, because the elderly have many chronic diseases, functional decline, cognitive impairment, dementia, and physical limitations. Preparedness is an action taken in anticipation of a disaster to ensure that the actions taken can be. This research is a quantitative study using the research design